Weld Effective Lengths for Rectangular HSS Overlapped K-Connections - Tousignant, Kyle; Packer, Jeffrey A. (Engineering Journal, 2015)
One large-scale, 33-ft-span, simply supported, Warren truss was tested to assess the performance of welds in rectangular hollow structural section (HSS) overlapped K-connections. Nine overlapped connections, within the truss, were designed to be weld-critical and sequentially failed by producing an axial force distribution with a point load, applied quasi-statically, to strategic panel points. The structural reliability (or safety index) of the existing AISC specification formulas for the effective length of welds in rectangular HSS overlapped K-connections, in Table K4.1 of the 2010 AISC Specification for Structural Steel Buildings, was determined from the tests. The results indicate that these provisions are conservative; hence, a modification to the current requirements that limits the effective width of the transverse weld elements is proposed. The proposal establishes a more economical and yet still safe weld design method for rectangular HSS overlapped K-connections.